KOEKSISTENSI DAN PERLINDUNGAN MASYARAKAT ADAT O'HONGANA MANYAWA DI WILAYAH PERTAMBANGAN NIKEL - Alting, Husen; Sinay, Siti Barora; Alwan, Sultan (Faculty of Law, Universitas Pekalongan, 2024)
Nickel mining in Halmahera, especially in Central Halmahera and East Halmahera Regencies, makes a major contribution to the national economy through the downstreaming of strategic minerals. However, these activities have serious impacts on the forest ecosystem and the lives of the O'Hongana Manyawa indigenous people, which relies heavily on their living space for cultural sustainability and livelihoods. This research aims to analyze the co-existence between mining activities and the protection of indigenous communities, with a focus on the legal framework, evaluation of protection practices. The research uses empirical legal methods through in-depth interviews, field observations, and secondary document studies. The research results show that the overlap of mining concession areas with the living spaces of indigenous communities causes environmental damage, social marginalization and loss of cultural identity. Existing regulations, such as AMDAL, do not fully protect the rights of indigenous peoples because their implementation is weak. Therefore, a more balanced approach is needed, such as recognition of traditional territories, application of the principles of Free, Prior and Informed Consent (FPIC), as well as empowerment programs based on local culture. In conclusion, protection of indigenous communities must be a priority to ensure social, cultural and ecological sustainability amidst industrial development.